Educational software for the formulation of research projects - Contreras Núñez, Joel (2023)
This article presents the results of the implementation of the educational software called Sistproy in the learning of university students of research subjects from the elaboration of the consistency matrix and results matrix oriented to the formulation of basic, applied and technological thesis projects. The quantitative research used a sample of 39 students of Electrical Engineering of the Continental University enrolled in the subject Research Workshop I, who were selected by non-random convenience sampling and then classified into experimental and control groups. It is concluded that the use of the educational software improves the students’ learning, detecting superiority in the scores obtained and notable progress in the elaboration of the thesis project.